2010
DOI: 10.1159/000286281
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Breast Cancer Subtypes in Patients with Brain Metastases

Abstract: Background: The principal objective of this study was to assess clinical outcomes by breast cancer subtype in patients with brain metastases. Methods: Estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor-2 (HER2) status was evaluated via immunohistochemical staining. Four survival time intervals were compared according to the subtype (ER+/HER2–, HER2+, triple negative (TN)). Results: 20 (30.3%) of the 66 patients in this study were ER+/HER2–, 20 (30.3%) were HER2+, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 18 publications
3
12
0
2
Order By: Relevance
“…This study adds to the considerable available literature reporting that brain metastases from breast cancer are heterogeneous and differ in terms of tumor biology and prognosis. Previous studies have demonstrated that HER2‐positive disease is a favorable prognostic factor in patients with newly diagnosed brain metastases 7‐11. Our study suggests that HER2 positivity also has prognostic significance at the time of CNS recurrence.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…This study adds to the considerable available literature reporting that brain metastases from breast cancer are heterogeneous and differ in terms of tumor biology and prognosis. Previous studies have demonstrated that HER2‐positive disease is a favorable prognostic factor in patients with newly diagnosed brain metastases 7‐11. Our study suggests that HER2 positivity also has prognostic significance at the time of CNS recurrence.…”
Section: Discussionsupporting
confidence: 63%
“…Previous studies have demonstrated that HER2-positive disease is a favorable prognostic factor in patients with newly diagnosed brain metastases. [7][8][9][10][11] Our study suggests that HER2 positivity also has prognostic significance at the time of CNS recurrence. This is likely reflective of effective systemic therapy options in the HER2-positive population.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…5 Breast cancer brain metastasis is the main source of metastatic brain disease in women, 40 and has a high mortality rate as a result of resistance to chemotherapies 2 and a low success rate of radiotherapy. 41 …”
Section: Discussionmentioning
confidence: 99%